2022
DOI: 10.1029/2021jc018123
|View full text |Cite
|
Sign up to set email alerts
|

Wind Profile in the Wave Boundary Layer and Its Application in a Coupled Atmosphere‐Wave Model

Abstract: Current models cannot capture well the impacts of wind waves on the atmospheric boundary layer. Here, we proposed a new turbulence closure model to estimate the wind stress in the wave boundary layer from viscous stress, shear‐induced turbulent stress, wind‐sea induced stress, and swell‐induced upward stress separately. The misalignment between the wind stress and wind is also considered in the model. Single‐column simulations indicate that (a) the swell‐induced upward momentum flux increases the surface wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…From this coupled model, it was noticed that the ocean‐side stress can differ significantly from the air‐side stress and their ratio decreases with increasing inverse wave age (Qiao et al., 2021). 30‐year wave hindcast data were used to investigate the redistribution of air‐sea momentum flux by waves (Wu et al., 2022), and showed a similar result. Due to limitations of the model in capturing the impact of wind waves in the atmospheric boundary layer, they proposed a new turbulence closure scheme, including the wind‐sea induced stress and the misalignment between the wind stress and the wind (Wu & Qiao, 2022), and showed that the surface wind can be altered by ocean surface waves by up to 5%.…”
Section: Air‐sea Momentum Flux: Wind Stressmentioning
confidence: 98%
“…From this coupled model, it was noticed that the ocean‐side stress can differ significantly from the air‐side stress and their ratio decreases with increasing inverse wave age (Qiao et al., 2021). 30‐year wave hindcast data were used to investigate the redistribution of air‐sea momentum flux by waves (Wu et al., 2022), and showed a similar result. Due to limitations of the model in capturing the impact of wind waves in the atmospheric boundary layer, they proposed a new turbulence closure scheme, including the wind‐sea induced stress and the misalignment between the wind stress and the wind (Wu & Qiao, 2022), and showed that the surface wind can be altered by ocean surface waves by up to 5%.…”
Section: Air‐sea Momentum Flux: Wind Stressmentioning
confidence: 98%